Incidencia de los programas educativos en los medios de comunicación audiovisuales para los estudiantes del Colegio Velasco Ibarra del cantón Buena Fe, año 2022 - Vergara Loor, Gabriela Gisella (2022)
This case study seeks the incidence that educational programs have in the media in the city of Buena Fe for the students of the Velazco Ibarra school in the Buena Fe canton, in turn, it seeks a relevance that is found in this case study because so a solution can be found. To search for information successfully, this work mixes documentary and biographical research of a descriptive methodology with a survey technique with its respective bank of questions in order to obtain information on how it approaches educational programs in the media. To understand the field, careful research and critical analyzes were carried out on the subject. With the completion of the project, it can be deduced that the educational programs, in addition to being something of great impact for the students of the Velazco Ibarra school, since it gives an improvement in teaching and involvement in the problematic support, it is worth mentioning that an analysis of the information was carried out. determined that there is an incidence for educational programs in the Buena Fe canton.